Gender-related power differences, beliefs and reactions towards people living with HIV/AIDS: an urban study in Nigeria - Mbonu, Ngozi C (BioMed Central, 2010)
BACKGROUND: Although there are an increasing number of studies on HIV-related stigma in Nigeria, very little research has focused on how power differences based on gender perpetuate the stigmatization of people living with HIV/AIDS (PLWHA) and how these gender differences affect the care that PLWHA receive in health care institutions. We explore gender-related beliefs and reactions of society, including health care professionals (HCPs), with regard to PLWHA, using Connell's theoretical framework of gender and power (1987). With Connell's structural theory of gender and power (financial inequality, authority and structure of social norms), we can describe gender differences in stigmatization of PLWHA. METHOD: We conducted in-depth semi-structured interviews, lasting 60 to 90 minutes, with 100 persons (40 members of the general public, 40 HCPs and 20 PLWHA) in Port Harcourt, Nigeria. The interviews were tape-recorded and transcribed verbatim. The Nvivo 7 computer package was used to analyze the data. RESULTS: There are similarities and differences between the general public and HCPs towards PLWHA in gender-related beliefs and reactions. For instance, although association with promiscuity and power differences were commonly acknowledged in the different groups, there are differences in how these reactions are shown; such as HCPs asking the female PLWHA to inform their partners to ensure payment of hospital bills. Women with HIV/AIDS in particular are therefore in a disadvantaged position with regard to the care they receive. CONCLUSION: Despite the fact that men and women with HIV/AIDS suffer the same illness, clear disparities are apparent in the negative reaction women and men living with HIV/AIDS experience in society. We show that women's generally low status in society contributes to the extreme negative reactions to which female PLWHA are subject. The government should create policies aimed at reducing the power differences in family, society and health care systems, which would be important to decrease the gender-related differences in stigma experienced by PLWHA. Interventions should be directed at the prevailing societal norms through appropriate legislation and advocacy at grassroots level with the support of men to counter laws that put women in a disadvantaged position. Furthermore, development of a policy that encourages equality in access to health care for all patients with HIV/AIDS by applying the same conditions to both men and women in health care institutions is recommended. There is a need to protect women's rights through implementing support policies, including paying attention to gender in the training of HCPs.